Biochemical characterization of three yellow cassava cultivars grown in the Republic of Congo - Ngounga, Célestine Kiminou; Loumouamou, Bob Wilfrid; Toumnou, Lucie Aba; Debora, Samba Kobesse Michelle; Bertin, Mikolo (Journal of Food Technology Research, 2025)
Cassava exists in two varieties: sweet and bitter. However, the Congolese population considers all yellow-fleshed cassava varieties as sweet, and they are eaten raw or boiled. A variety is considered sweet if its hydrocyanic acid content is less than 50 mg/kg. The objective of this study is to characterize the three most consumed yellow-fleshed cassava varieties in Congo, namely Mboto, Dikondi, and Nkaba yellow varieties. Hydrocyanic acid and beta-carotene were measured by spectrophotometry. Water, dry matter, crude ash, lipid, titratable acidity, and pH were determined according to the Association of Official Analytical Chemists. Total crude fiber and protein were measured by the Weende and Kjeldahl methods, respectively. The analyses carried out on the three cultivars "Mboto, Dikondi, Nkaba yellow" revealed the following contents: hydrocyanic acid: 33.49, 42.75, and 121.24 mg.kg-1; water: 89.33, 70.02, and 58.96%; dry matter: 10.74, 29.98, and 41.04%; ash: 2.53, 1.68, and 2.78%; protein: 2.48, 2.01, and 1.98%; lipids: 0.27, 0.59, and 2.89%; fiber: 10.8, 2.4, and 2.4%. The ẞ-carotene contents: 1.58, 0.39, and 0.84 µg/g; energy values: 35.00, 123.73, and 171.90 kcal/100g. These results show that among the three varieties, the yellow Nkaba is a bitter variety and cannot be eaten raw.